PD-L1 maintains neutrophil extracellular traps release by inhibiting neutrophil autophagy in endotoxin-induced lung injury - Zhu, Cheng-long; Xie, Jian; Zhao, Zhen-zhen; Li, Peng; Liu, Qiang; Guo, Yu; Meng, Yan; Wan, Xiao-jian; Bian, Jin-jun; Deng, Xiao-ming; Wang, Jia-feng (Frontiers in Immunology, 2022)
Programmed death ligand 1 (PD-L1) is not only an important molecule in mediating tumor immune escape, but also regulates inflammation development. Here we showed that PD-L1 was upregulated on neutrophils in lipopolysaccharide (LPS)-induced acute respiratory distress syndrome (ARDS). Neutrophil specific knockout of PD-L1 reduced lung injury in ARDS model induced by intratracheal LPS injection. The level of NET release was reduced and autophagy is elevated by PD-L1 knockout in ARDS neutrophils both in vivo and in vitro. Inhibition of autophagy could reverse the inhibitory effect of PD-L1 knockout on NET release. PD-L1 interacted with p85 subunit of PI3K at the endoplasmic reticulum (ER) in neutrophils from ARDS patients, activating the PI3K/Akt/mTOR pathway. An extrinsic neutralizing antibody against PD-L1 showed a protective effect against ARDS. Together, PD-L1 maintains the release of NETs by regulating autophagy through the PI3K/Akt/mTOR pathway in ARDS. Anti-PD-L1 therapy may be a promising measure in treating ARDS.